EXAMINATION OF THE RELATIONSHIP BETWEEN PHYSICAL ACTIVITY PARTICIPATION MOTIVATION AND DIGITAL GAME PLAYING MOTIVATION - Gökyürek, Belgin (Acta Scientiae et Intellectus, 2024)
This study was carried out to examine the motivation of secondary school students to participate in physical activity and play digital games. Scanning design, one of the descriptive research models, was used in the study. The study group consisted of 462 students continuing their education in secondary schools in Ankara province Çankaya district in the 2022-2023 academic year. In the study, the Digital Game Playing Motivation Scale (DGPMS) developed by Demir and Hazar (2018) and the Motivation scale for participation in physical activity (MSPPA) developed by Demir and Cicioğlu (2018) were used. In scientific analysis, arithmetic mean, standard deviation, percentage, frequency, Spearman Correlation, Mann-Whitney U Test, Kruskal-Wallis Tests were used. In the study, a low-level significant negative correlation was found between the MSPPA total score, achievement and arousal, curiosity and social acceptance sub-dimensions. Significance was found in favor of male students in the sub-dimensions of success and vitality and curiosity and social acceptance according to gender. According to the grade level variable, a significant difference was found in favor of the 6th grades in the sub-dimensions of achievement and arousal, curiosity and social acceptance. In the research, it was seen that the motivation of the participants to play digital games was medium, and the motivation to participate in physical activity was high. As a result of the research, it was found that as the motivation to participate in physical activity increased, the desire of individuals to play digital games and the motivation to have fun through digital games decreased.